Etika Komunikasi Dalam Memfasilitasi Kepemimpinan Berdasarkan Nilai Agama Dalam Organisasi - Iskandar Zulkarnaen; Alvin Dwi Nugroho; Ismail Mubarok (Student Scientific Creativity Journal, 2024)
Religious values aare very important in education. These values also influence the way everyone behaves in the organization. Religious values such as human connection with Allah SWT, the seriousness of conscience, and other religious values are internalized as part of the organizational culture. Apart from that, research has shown that the application of Islamic values in organizational culture such a worshio, trust, responsibility, fairness, ihsan, mutual hep, makes organizations more Islamic. Overall, religious values, especially in the Islamic context, provide a strong moral and ethical foundation for building organization that are sustainable, humane and full of good vibes.